ОСОБЕННОСТИ РАСПРЕДЕЛЕНИЯ БАКТЕРИОПЛАНКТОНА В РАЙОНАХ ПОДНЯТИЙ ДНА ЮЖНОЙ АТЛАНТИКИ - (:unkn) unknown (Киев : Наукова думка, 1986)
Изучали распределение бактериопланктона методом прямого счета в районах банок Дейвис, Модельная, Вальдивия и Удачная. Численность бактерий в поверхностном горизонте исследованных акваторий колебалась от 382 тыс. (банка Дейвис) до 1452 тыс. кл·мл-1 (банка Удачная). Пространственные изменения численности бактерий связаны с гидрологическими особенностями изученных районов. Непосредственно над вершинами банок отмечено уменьшение количества бактерий.
Peculiarities of the bacterioplankton distribution in the regions of bottom elevations in the South Atlantics
In the regions of the oceanic bottom elevations in the South Atlantics the quantity of bacteria was within the range of 382-1452 thou. cells/ml-1 in the surface level. The Deivis and Modelnaya banks in the oligotrophic waters of the Brazil current were poorer than the Valdiviya and Udachnaya banks located in zones of the current interaction and differing in the complicated hydrological structure of waters. The quantity of bacteria was observed to decrease over heads of all the banks.